2021
DOI: 10.1063/5.0053649
|View full text |Cite
|
Sign up to set email alerts
|

On the exceptional temperature stability of ferroelectric Al1-xScxN thin films

Abstract: Through its dependence on low symmetry crystal phases, ferroelectricity is inherently a property tied to the lower temperature ranges of the phase diagram for a given material. This paper presents conclusive evidence that in the case of ferroelectric Al1−xScxN, low temperature has to be seen as a purely relative term, since its ferroelectric-to-paraelectric transition temperature is confirmed to surpass 1100 °C and thus the transition temperature of virtually any other thin film ferroelectric. We arrived at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 42 publications
(29 reference statements)
4
37
0
Order By: Relevance
“…The data for the AlN TCC are in reasonable agreement with previous reports on the AlN single crystals of 74-79 ppm/ C, over a similar temperature range. 16 Monotonic trends in dielectric constant over this temperature range are consistent with the reports of Fichtner et al and Islam et al, who suggested that the film remained polarized (i.e., no paraelectric phase transitions) for temperature excursions up to 1100 C. 5,17 The loss tangent slightly increases with temperature, which also introduces a weak frequency dependence to the relative permittivity. These observations are consistent with an increase in space charge polarizability at elevated temperatures, as is expected for all dielectrics.…”
supporting
confidence: 87%
“…The data for the AlN TCC are in reasonable agreement with previous reports on the AlN single crystals of 74-79 ppm/ C, over a similar temperature range. 16 Monotonic trends in dielectric constant over this temperature range are consistent with the reports of Fichtner et al and Islam et al, who suggested that the film remained polarized (i.e., no paraelectric phase transitions) for temperature excursions up to 1100 C. 5,17 The loss tangent slightly increases with temperature, which also introduces a weak frequency dependence to the relative permittivity. These observations are consistent with an increase in space charge polarizability at elevated temperatures, as is expected for all dielectrics.…”
supporting
confidence: 87%
“…To assess polarization stability for a nonvolatile memory, Islam et al poled the sample at room temperature (RT), baked the package at 1100 • C, and remeasured the P r once cooled back to RT [23]. While promising for an NVM since the polarization state is maintained after exposure to extreme temperatures, these ex situ results did not address the P r or switching behavior at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The wurtzite-type crystalline structure of Al 1−x Sc x N deposited on molybdenum (Mo) bottom electrodes was demonstrated to be stable even at 1298 K for thicknesses above 400 nm. 19,20 Temperature-dependent electrical measurements of the ferroelectric properties in Al 1−x Sc x N pointed out a strong reduction of the coercive field as well as an impressive P r stability with increasing temperature up to 673 K. 21−26 All previous reports on the temperature stability of ferroelectric properties in Al 1−x Sc x N consider films with a thickness above 200 nm. The only exception is the work of Mizutani et al, 26 in which the maximum temperature investigated is 523 K. However, a complete study combining both material characterization and electrical techniques for high temperatures is still missing in films with a thickness below 200 nm.…”
Section: Introductionmentioning
confidence: 99%